2014
DOI: 10.1371/journal.pone.0104568
|View full text |Cite|
|
Sign up to set email alerts
|

Pleiotropic Functions for Transcription Factor Zscan10

Abstract: The transcription factor Zscan10 had been attributed a role as a pluripotency factor in embryonic stem cells based on its interaction with Oct4 and Sox2 in in vitro assays. Here we suggest a potential role of Zscan10 in controlling progenitor cell populations in vivo. Mice homozygous for a Zscan10 mutation exhibit reduced weight, mild hypoplasia in the spleen, heart and long bones and phenocopy an eye malformation previously described for Sox2 hypomorphs. Phenotypic abnormalities are supported by the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…loss-of-function mutation exhibited pleiotropic outcomes, affecting numerous physiological systems including but not limited to the renal, cardiovascular, respiratory, and the immune systems (Kraus et al, 2014). However, there have yet to be any reports of the functional consequences of Zscan10 overexpression, and as such the link to embryonic growth identified in this chapter is novel.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…loss-of-function mutation exhibited pleiotropic outcomes, affecting numerous physiological systems including but not limited to the renal, cardiovascular, respiratory, and the immune systems (Kraus et al, 2014). However, there have yet to be any reports of the functional consequences of Zscan10 overexpression, and as such the link to embryonic growth identified in this chapter is novel.…”
Section: Discussionmentioning
confidence: 80%
“…Zscan10 is best known for its role in regulating embryonic stem cell development (Zhang et al, 2006), but it has been proposed that it may continue to regulate progenitor cells for the remainder of embyronic development and postnatal life (Kraus et al, 2014). Mice homozygous for a Zscan10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, we may be detecting the impression left by a protein on the structure of DNA, several decades after the fact (Ziller et al, 2015). To that end, there is evidence supporting a role for ZSCAN10 in maintaining a multipotent progenitor cell population in mid-gestation embryos and adult organs (Kraus et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it was also reported that Zscan10 might act as a transcriptional activator of the 2-cell-stage specific transcripts, such as Zscan4 and Tcstv1, because their expression levels are decreased in Zscan10 knocked-down ES cells [5]. In contrast, it was recently reported that Zscan10 knockout mice can develop to adult organisms although they have some defects such as weight reduce or eye defect [9], suggesting that its function for the maintenance of the pluripotent cell population in early developmental process is either dispensable or masked by the maternal transcripts. In the previous reports that applied shRNA-mediated knock-down strategy for the loss of function experiments, 10-20% of total Zscan10 transcripts still remained [4,5].…”
Section: Introductionmentioning
confidence: 99%